Tatu a guidebook for tattoo and body pierces. (Remedios AIDS Foundation, 2002)
Contents: Information about tattoo and body pierces. Protection from all types of blood borne infections, including HIV/AIDS, that is affordable to both clients and practitioners. Glossary of terms. Bibliography.